Transcriptome Analysis of Myzus persicae to UV-B Stress - Yang, Chang-Li; Meng, Jian-Yu; Yao, Meng-Shuang; Zhang, Chang-Yu (Journal of insect science (Tucson, Ariz.), 2021)
As an environmental stress factor, ultraviolet-B (UV-B) radiation directly affects the growth and development of Myzus persicae (Sulzer) (Homoptera: Aphididae). How M. persicae responds to UV-B stress and the molecular mechanisms underlying this adaptation remain unknown. Here, we analyzed transcriptome data for M. persicae following exposure to UV-B radiation for 30 min. We identified 758 significant differentially expressed genes (DEGs) following exposure to UV-B stress, including 423 upregulated and 335 downregulated genes. In addition, enrichment analysis using the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes databases illustrated that these DEGs are associated with antioxidation and detoxification, metabolic and protein turnover, immune response, and stress signal transduction. Simultaneously, these DEGs are closely related to the adaptability to UV-B stress. Our research can raise awareness of the mechanisms of insect responses to UV-B stress. Graphical Abstract